Biochemical characterisation of dystrophin in sensory dendrite and epithelial cells of drosophila melanogaster - Wei, Tee Chee (2020)
Contact-mediated self-avoidance/repulsion restricts dendrites of sensory neuron in a 2D space. Defect in dendrite-extracellular matrix (ECM) adhesion disrupts the confinement and results in self-crossing of dendrites in a 3D space. In addition, these complex and diverse patterns of sensory neurons innervate the epidermis and muscle. However, the mechanisms governing dendrite patterning are still poorly understood. The objectives of this study are to uncover and characterise a novel gene in epithelial cells regulating dendritic morphology of sensory neurons in Drosophila third instar larvae. First of all, the genetic background of selected Drosophila mutant lines: adenomatous polyposis coli, dystroglycan and dystrophin was standardized by backcrossing to the wild type strain and then identified by using non-lethal PCR genotyping method from Drosophila wings. In this study, dystrophin in epithelial cells was found underlying the dendritic morphology of sensory neurons in Drosophila third instar larvae. Mutations or RNAi knockdown of dystrophin in epidermal cells were led to an increase in dendritic self-crossing of sensory neurons. In contrast, normal phenotype of dendrite morphology was exhibited upon RNAi knockdown or transgenic expression of dystrophin in neurons. Surprisingly, transgenic expression of dystrophin Dp186 in epidermal cells exacerbated its mutant phenotype, instead of rescuing it. Analysis of dendrite-ECM adhesion with highresolution confocal microscopy and fluorescent-labelled markers in third instar larva corroborated that the reduction of dystrophin in epidermal cells promoted dendrites to be detached from the ECM. Computational analysis predicted the majority of Dystrophin isoforms contained microtubule-binding domain, which was responsible for direct binding of microtubules. Immunofluorescence of DmD8 cells and larval epidermal cells of Drosophila observed a colocalization of Dystrophin Dp186 and microtubules, but devoid of microtubule-binding domain of Dystrophin Dp186 did not associate with microtubules. Here, in vivo results were inconclusive due to technical problems: inclusion body formation by overexpression of Dystrophin Dp186 and the limited resolution power of confocal microscopy on microtubules. However, in vitro assay confirmed that bacterial produced Dystrophin Dp186 binds microtubules directly through its microtubule-binding domain. In future, further indepth study is required to elucidate the role of Dystrophin in coordinating sensory dendrite arborization.